Carbon Accounting and Ethical Dilemmas in Emission Reporting: Between Compliance and Greenwashing - Nada Cantika Putri Kadua (Pt. Anagata Sembagi Education, 2025)
This study examines the ethical dilemma inherent in corporate carbon accounting and emissions reporting, particularly the tension between substantive regulatory compliance and strategic greenwashing. Increasing regulatory pressure and global net-zero commitments have positioned carbon disclosure as a core instrument of corporate governance; however, persistent weaknesses in measurement quality, disclosure integrity, and governance structures have generated substantial ethical challenges. This research adopts a qualitative explanatory design using systematic literature review and document analysis of 72 academic studies, regulatory reports, corporate sustainability disclosures, and enforcement cases published between 2020 and 2025. Data were analyzed through thematic content analysis and comparative institutional analysis. The results reveal that dominant corporate practices include incomplete Scope 3 reporting, selective and promotional disclosure, symbolic compliance, weak governance, and long-term net-zero targets lacking operational implementation. The findings further demonstrate a strong inverse relationship between regulatory strength and greenwashing intensity, indicating that robust climate governance and mandatory reporting significantly reduce opportunistic disclosure behavior. The discussion highlights how economic incentives, market expectations, regulatory design, and professional standards jointly shape the ethical trajectory of carbon accounting. The study concludes that carbon accounting functions either as a mechanism of genuine climate accountability under strong institutional governance or as a sophisticated instrument of greenwashing under weak regulatory environments, underscoring the need for institutional strengthening to achieve sustainable corporate climate governance.